Psychologické aspekty gynekologických operací - Váchová, D; Martan, A; Líbalová, Z; Cepický, P (Ceska gynekologie, 2001)
OBJECTIVE: To make the stress influence of the hospitalisation on patients objective, to determine the factors in the process of therapy, which negatively influence a patient, and to find the consequences between the intensity of anxiety and the occurrence of the post-operational complications followed by the lengths of hospitalisation. DESIGN: Prospective clinical study. SETTING: The Department of Gynecology-Obstetrics of the General Teaching Hospital and the 1 st. Medical Faculty of the Charles University in Prague. METHODS: 63 patients after the planned middle serious operation (abdominal or vaginal hysterectomy, Burche suspension and vaginal plastics) were included into the study. The women were not treated both because of oncological or psychiatric reasons and they did not suffer from some other serious illness. The mean age was 53, mean weight 72 kg and mean parity 1.7. Evaluation of the stress influence of the patients was performed by means of the questionnaires, which were devised by us (Questionnaire A and B), and by means of standard questionnaires (STAI, SCL-90) that were filled in by the patients on the day of their reception and on the day of their release from the hospital. RESULTS: By evaluation of the questionnaires we have received objective parameters of the measure of anxiety and stress the patient is entering the treatment process with, and also subjective evaluation of the concrete stress moments occurring during the hospitalisation. A hypotheses proving that the more the stress load experienced by a patient the higher the probability of the occurrence of complications in the post-operational period and consequently longer hospitalisation has been verified by the methods of the statistic analyses. For our clinical praxis, the results of the descriptive analyses, where our patients evaluated their fear concerning the illness, its operational resolution and particular stress situations during hospitalisation, are mainly important. CONCLUSION: Our results proved that for ensuring optimal course of operation and post-operational period it is most important to reduce stress influence on a patient, i.e. particularly by a personal discussion of a surgeon and a treating doctor with the patient, and by elimination of the negative factors during the period of hospitalisation. Last but not least the most important role plays the clinical psychologist because not only important is professional medical, but also psychological access to the patient.
Keywords: gynekologické chirurgické výkony; průzkumy a dotazníky; Female; úzkost; ženské pohlaví; psychický stres; Surveys and Questionnaires; lidé; pooperační komplikace; Anxiety; délka pobytu; Length of Stay; prospektivní studie; Postoperative Complications; Prospective Studies; Gynecologic Surgical Procedures; lidé středního věku; Middle Aged; Stress, Psychological; Humans